Effects of Moringa oleifera aqueous seed extracts on reproductive traits of heat-stressed New Zealand white female rabbits - Mutwedu, Valence B.; Nyongesa, Albert W.; Kitaa, Jafred M.; Ayagirwe, Rodrigue B. B.; Baharanyi, Chasinga; Mbaria, James M. (Frontiers in Veterinary Science, 2022)
This study was initiated to evaluate the efficacy of Moringa oleifera aqueous seed extract (MOASE) on reproductive performances, hormonal profile and ovary histology in the management of heat stress in female rabbits. Twenty-eight rabbits with 6 months old and weighing between 2015.6 and 2322.7 g were randomly assigned to four different batches in terms of temperature, relative humidity, temperature and humidity index (THI) and MOASE. The batches were respectively defined as follows: T0: room temperature (18-24°C), relative humidity (59 ±0.48%), and 23.6 ±1.52 as THI. For T1, T2, and T3: 35-36°C, 64 ±0.6%, and 32.5 ±0.7 were respectively associated with 100, 200, and 0 mg/kg b.w. MOASE. Heat was induced in each rabbit cage, using electrical heaters from 08:00 h to 16:00 h. Reproductive performances related to female rabbits, kids and milk production were recorded. After 80 days, all animals were sacrificed, blood collected for hormones evaluation and ovary collected for histology. Results revealed a significant decrease (P<0.05) in feed intake, body weight and body weight gain in pregnant and lactating female rabbits exposed to heat stress. It was also observed a decrease in fur removal at parturition and litter size from birth to weaning, litter weight, kit body weight and kit weight gain in heat-stressed rabbits, weekly milk yield and daily milk efficiency, Estradiol, LH, FSH, Cortisol in heat-stressed female rabbits compared to the control. However, administration of MOASE at 200mg.kg b.w. increased (P<0.05) these parameters. An increase (P<0.05) in the number of services per conception, milk intake and progesterone level was observed while administration of MOASE significantly (P<0.05) decreased these parameters. Ovarian histology of animals from T0 and T2 have similar structures with normal ovaries. In conclusion, heat stress induced reproductive performances in female rabbits. However, the administration of MOASE at 200 mg/kg b.w can mitigate these adverse effects.